2019
DOI: 10.1021/acs.orglett.9b01725
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of an Immunogenic Trehalose Phospholipid from Salmonella Typhi and Elucidation of Its sn-Regiochemistry by Mass Spectrometry

Abstract: Diphosphatidyltrehalose (diPT) is an immunogenic glycolipid, recently isolated from Salmonella Typhi. Despite rigorous structure elucidation, the sn-position of the acyl chains on the glycerol backbone had not been unequivocally established. A stereoselective synthesis of diPT and its regioisomer is reported herein. Using a hybrid MS3 approach combining collisional dissociation and ultraviolet photodissociation mass spectrometry for analysis of the regioisomers and natural diPT, the regiochemistry of the acyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Our initial approach to alcohol 2 utilized the catalytic epoxide opening reaction used by the Minnaard group to synthesize lipids with mixed acyl tails. 41,42 Through modification of the procedure initially published by the Jacobsen group on this transformation, 43 we were able to get this reaction to proceed with the solid Cbz-Lys(Cbz)-OH. The product of this reaction may be prone to migration on silica gel, 44 so the secondary hydroxyl group was protected with benzyl chloroformate (CbzCl)/tetramethylethylenediamine (TMEDA) prior to isolation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial approach to alcohol 2 utilized the catalytic epoxide opening reaction used by the Minnaard group to synthesize lipids with mixed acyl tails. 41,42 Through modification of the procedure initially published by the Jacobsen group on this transformation, 43 we were able to get this reaction to proceed with the solid Cbz-Lys(Cbz)-OH. The product of this reaction may be prone to migration on silica gel, 44 so the secondary hydroxyl group was protected with benzyl chloroformate (CbzCl)/tetramethylethylenediamine (TMEDA) prior to isolation.…”
Section: Resultsmentioning
confidence: 99%
“…45 Unfortunately, 1 H NMR analysis of 4 revealed that it contained a ∼3 : 1 mixture of regioisomers (4a : 4b) which was unexpected considering that this reaction proceeds with complete regioselectivity when aliphatic acids are used (Scheme 2). [41][42][43] Attempts to improve the regioselectivity by increasing the number of equivalents of base or running the reaction at 0 °C were unfruitful. Reactions between protected amino acids and terminal epoxides are not common in literature, but we did find an example of a totally Cbz protected L-DOPA analog reacting with glycidol via tetrabutylammonium iodide (TBAI) catalysis to give a single regioisomer.…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to determine the binding target of the CAP1 and CAP3 phages. To do this, we constructed targeted deletions in the LH6 genome by replacing the gene homologs of pglC (initiating glycosyltransferase for O-glycans and CPS), pilA (pilin protein subunit), lpsC (LOS core glycosyltransferase) and clsB (cardiolipin synthase B or trehalose-phospholipid biosynthesis) [ 27 ] with an Acinetobacter -compatible kanamycin cassette. Although LH6 can readily take up plasmids with compatible origins of replication, such as pBAV1K-T5- gfp [ 7 ] and pAT4, it required the induction of an exogenous plasmid-encoded RecAB to undergo homologous recombination with the pglC pGEM knockout construct since electroporation without induction of RecAB yielded no transformants after repeated attempts.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has developed a powerful MS technique for GPL characterization by using ultraviolet photodissociation (UVPD). , UVPD has been shown to reveal minor structural differences in even the most complex lipid classes, ranging from fatty acids and simple GPLs ,, to the more complex GPLs such as cardiolipins and even LPSs . The strategy has characterized a number of structural features of GPLs, such as the presence and locations of cyclopropane and double bond ,,, unsaturations in acyl chains as well as sn-positions. ,, Here we employ high-resolution 193 nm UVPD-MS coupled to LC to uncover novel GPL modifications including hydroxyl-modified acyl chains and methylated PS headgroups. Additionally, we use this approach to elucidate specific trends in the unsaturation patterns of bacterial GPLs using an array of 12 bacterial extracts and provide the first direct evidence of aminoacyl-PGs (aa-PGs) in Gram-negative Campylobacter jejuni .…”
mentioning
confidence: 99%
“…62 The strategy has characterized a number of structural features of GPLs, such as the presence and locations of cyclopropane 17 and double bond 18,60,63,64 unsaturations in acyl chains as well as sn-positions. 18,65,66 Here we employ high-resolution 193 nm UVPD-MS coupled to LC to uncover novel GPL modifications including hydroxyl-modified acyl chains and methylated PS headgroups. Additionally, we use this approach to elucidate specific trends in the unsaturation patterns of bacterial GPLs using an array of 12 bacterial extracts and provide the first direct evidence of aminoacyl-PGs (aa-PGs) in Gram-negative Campylobacter jejuni.…”
mentioning
confidence: 99%